Adopting strategic intervention in substantiating university functions: identifying the components of university-community engagement - Md Yunus, Aida Suraya; Azman, Norzaini; Shuib, Munir; Abdul Rahim, Asyirah; Masron, Tarmiji (Sage Publications, 2019)
Education in Malaysia adopts a continuous process for developing physical, emotional, spiritual, and intellectual capacity of individuals. Such are the core components in Malaysia’s National Education Philosophy, befitting the functions of university which focus on developing the intellectual, educational, and social capacity among individuals in the society. That said, a university’s activities involve the participation of various levels and groups in the community. This paper reports the qualitative findings of a study which identified the components of university-community engagement (UCE) concept, being aware of the absence of its proper study despite the nation-wide UCE implementation. Input from eminent higher education leaders, school students, business community and non-governmental organization have been gathered, leading to the identification of components of university-community engagement. This has shed light on the approaches to be taken by universities in substantiating their strategic interventions to develop impactful UCE initiatives.